The economics of converting a sheep farm into a springbuck (Antidorcas marsupialis) ranch in Graaff-Reinet: a simulation analysis - Dlamini, Thula Sizwe (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2026)
In Graaff-Reinet, domestic livestock farming and springbuck ranching are similar in that they both rely on the rangeland for their sustainability. However, as a consequence of repeated monotonous domestic livestock farming, resulting in compromised biological productivity and diversity, the rangelands have disintegrated. This, unfortunately, has placed the future sustainability of these rangelands and the livelihoods of the local people in an indeterminate state. In recent years, there has been an increasing interest in springbuck ranching for meat production as an alternative to domestic livestock farming in the area following (a) fears of worsening environmental challenges
Keywords: Livestock projects -- South Africa -- Eastern Cape; Livestock productivity -- South Africa -- Eastern Cape; Livestock -- Economic aspects -- South Africa -- Eastern Cape; Sheep -- Breeding -- South Africa -- Eastern Cape; Springbok -- Breeding -- South Africa -- Eastern Cape